From prison gangs to transnational mafia: the expansion of organized crime in Brazil - Stahlberg, Stephanie G. (Trends in organized crime, 2022)
This article uses quantitative and qualitative data to document the alarming expansion of the three largest organized criminal groups (OCGs) in Brazil, the Primeiro Comando da Capital (PCC), Comando Vermelho, and Família do Norte. It employs a novel dataset comprised of Google search queries about each criminal organization, and uses search interest as a proxy for OCG activity in a given state and year. The results show that the PCC has grown the most, well established in its headquarters of São Paulo state and now present in all other states in Brazil. Interviews reveal that over the course of almost three decades, the PCC has evolved from a prison gang to a transnational proto-mafia: it has linked and gained control over the entire drug supply chain that crosses Brazil. In addition, the PCC is able to directly challenge the state, and it controls prisons and community enclaves where it imposes its own model of criminal governance. These findings call attention to a concerning scenario for the Brazilian state and society as organized crime grows in size and power.